JEWELRY FROM THE PERSPECTIVE OF NEW MEDIA RESEARCH ON MARKETING STRATEGY - Jin Lili; Wan Farha Binti Wan Zulkiffli (International Journal of Accounting, Finance and Business, 2022)
With the rapid development of Internet technology, the forms of information transmission become diversified, and the way of marketing is also iterated. On the one hand, many individuals and enterprises have benefited from the change from one-way release of information through media to "we media". On the other hand, as the Internet has changed the way people shop and more and more consumers have personalized needs when choosing products, the marketing methods of all walks of life have gradually changed from product-oriented to demand-oriented. As a traditional industry, jewelry industry has also changed its marketing methods in accordance with the trend of The Times. The development of new media has greatly enriched its display methods and promoted the dissemination of cultural and emotional values of jewelry. Therefore, it is of great significance to study jewelry marketing strategies from the perspective of new media.The change of marketing mode largely benefits from the rapid development of the Internet. In the traditional marketing mode, the product-oriented one-way marketing makes the whole brand influence path as visibility -- reputation -- loyalty. The retention of consumers is like a great wave washing the sand, which will be filtered through layers of funnel structure. New media platform integration of upgrade and the advantage of new media itself makes other industries have a media properties, interactive marketing methods to attract the idea with the brand or product corresponds to the consumers, to consumer demand as the guidance of integrated marketing in imperceptible in saturated with brand product information, affect the audience's cognitive and attitude, The whole influence path is reversed into loyalty -- reputation -- popularity.this paper studies the current jewelry industry's new media marketing strategies and problems, and puts forward corresponding suggestions, which provide theoretical support for deepening the research on new media marketing in the jewelry industry.